Intra-grade variability in educational and psychosocial competencies of school going adolescent girls, in the coastal region of Kenya: implications for school based interventions - Beth Kangwana; Eunice Muthengi; Karen Austrian (BMC, 2020)
Abstract Background The onset of puberty and menarche is a potentially vulnerable time for girls. Educational and psychosocial competencies are regarded as essential tools that empower them to successfully navigate the adolescent years. The aim of this study is to evaluate to what extent school going girls are equipped with these key competencies, and how they vary across a given grade cohort. Methods Data was collected in Kilifi County, Kenya, from 140 public primary schools from grade 7, across three sub-counties. Bivariate and multivariate analyses were carried out to compare competency outcomes by age groups comprising 10-14 years and 15 year and above. Generalized estimating equations with robust standard errors was used where outcomes were measured as binary outcomes, and linear regression for continuous outcomes. Clustering was factored in at the school level and stratification at the subcounty level. Wilcoxon Rank sum test incorporating clustering effects was used where continuous outcomes were not normally distributed. Results A total of 3489 adolescent girls were interviewed with a mean age of 14 years (SD:1.5; min:10, max:21). Compared to the lower age group, girls in the higher age group were less likely to have ambitions of furthering their education beyond secondary school (odds ratio (OR):0.63 (95%CI:0.53, 0.74)), more likely to report not feeling confident enough to answer questions in class (OR:1.18 (95%CI:1.02, 1.36) and scored lower on their cognitive, math and literacy tests. They also displayed less positive gender norms (coefficient (coeff):-0.091 (95%CI:-0.16, − 0.022)) and were more likely to agree with intimate-partner violence in marriage (coeff:1.17 (95%CI:1.00, 1.37)). They however scored higher on the decision-making scale (coeff:0.36 (95%CI:0.13, 0.60)) and were more likely to be able to spontaneously name a method of modern contraception (OR:1.56 (95%CI:1.36, 1.80)). Conclusion Large variability in age exits within a grade. Compared to older girls, younger girls were more likely to perform better on their educational and social competencies. In countries with large age ranges per grade, identifying the presence of educational and psychosocial competency variabilities will allow informed decisions to be made on how school-based interventions should be adapted to address the varying needs within a grade. Trial registration ISRCTN10894523 , date of registration: 22/08/2017. Retrospectively registered.